Александра Последович: графика / О. П. Воронова - Воронова Ольга Порфирьевна (Советский художник, 1984)
Экземпляры: ИСК (20120524) / Инвентарный номер: 827821 / Цена: 1.60 / Сис.шифр: 85.153(2)-8 / Авт.знак: В 75 / ГРНТИ: 18.31.41 / ББК: 85.153(2=Рус)6-8